Sistem Elektro Pneumatik Modul PLC 3 Silinder Kerja Ganda Gerak Berlawanan - Ari Kurniawan; Hilda Porawati (LPPM Politeknik Jambi, 2020)
In the industrial application, the pneumatik system was used to help the production process that uses automatic control. The pneumatik system trainer that already exists in the Politeknik Jambi workshop still uses a manual control system. In this discussion, the writer wants to modify the PLC-based electro-pneumatik policy (programmer logic controller). Pneumatik systems were all systems that use power in the form of compressed air and are used to produce work. The first compressed air by the compressor and stored in the storage tube. The storage air was treated so that the pneumatik system can function correctly. The compressed air was regulated for use by a pneumatik control system, which is connected to the solenoid valve to drive three cylinders of double-acting opposite motion..